Genome-Wide Association Study of Meat Quality Traits in a Three-Way Crossbred Commercial Pig Population - Gao, Guangxiong; Gao, Ning; Li, Sicheng; Kuang, Weijian; Zhu, Lin; Jiang, Wei; Yu, Weiwei; Guo, Jinbiao; Li, Zhili; Yang, Chengzhong; Zhao, Yunxiang (Frontiers in Genetics, 2021)
Meat quality is an important trait for pig breeding programs aiming to meet consumers’ demand. It is necessary for geneticists to improve meat quality based on understandings of the underlying genetic mechanisms. Previous studies had showed that most indicators of meat quality were low to moderate heritability traits, so that improving meat quality by conventional technics remains a challenge. In this study, a genome-wide association study of meat quality traits was performed using the GeneSeek Porcine SNP50K BeadChip in 582 crossbred Duroc×(Landrace×Yorkshire) commercial pigs, including 249 males and 333 females. Meat conductivity, marbling score, moisture, meat color, pH value, and intramuscular fat content (IMF) were investigated. The genome-wide association study was performed by using both FarmCPU and MLM model with rMVP software. The genomic heritability of the studied traits ranged from 0.13±0.07 to 0.55±0.08 for conductivity and meat color, respectively. Thirty-two SNPs were identified for meat quality in crossbred D(LY) pigs using both FarmCPU and MLM model. Among the detected SNPs, 5, 9, 7, 4, 6, and 5 were significantly associated with conductivity, IMF, marbling score, meat color, moisture and pH value, respectively. Furthermore, several candidate genes for meat quality were identified in the detected genomic regions. These findings will contribute to the ongoing improvement of meat quality, meet consumer demand and improve economic outlook for swine industry.